PENGARUH KUALITAS PELAYANAN DAN MINAT TERHADAP LOYALITAS NASABAH PADA PRODUK TABUNGAN ISLAMIC BANKING (iB) HASANAH DI KCP BNI SYARIAH KEPANJEN - Tri Wahyuningtyas; Hilda Sanjayawati (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2022)
Customer loyalty is a top priority in this study because the level is getting sharper among banking companies in Indonesia. The main thing so that companies can survive, compete and dominate the market, the quality of service and interest must be improved. Banks must pay attention to the things that are considered important by customers. So that customers feel comfortable and do not switch to other banks. The purpose of this study was to determine and analyze the influence of service quality and interest variables on customer loyalty to the iB Hasanah savings product.